Archeologia krajowa na łamach „Tygodnika Ilustrowanego” do 1886 roku - Jeleń, Aleksandra (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
“Tygodnik Ilustrowany”, one of the most popular Warsaw periodicals, was coming out between 1859–1939. The aim of its founders was to create a magazine that would address national issues, including our past. The historical section, in which archeological topics found a place, was visible part of the “Tygodnik Ilustrowany”. The first editor of the magazine, Ludwik Jenike, for 27 years of managing the Warsaw periodical (that is the whole discussed period) never decided to limit publications connected with antiquity. However the archeological issues did not find a permanent place in the magazine. The following antiquarians were writing for the “Tygodnik Ilustrowany”: Józef Łepkowski, Franciszek Maksymilian Sobieszczański, Wacław Szymanowski, Kazimierz Władysław Wójcicki, Józef Ignacy Kraszewski. It must be underlined that the published information on archeological topics was not limited just to the news about excavations or accidental discoveries. The scholars’ and collectors’ biographical entries with precise descriptions of their findings as well as information on ancient exhibitions and museums that gather the monuments from prehistoric times were also included in the “Tygodnik Ilustrowany”. The history was treated with all seriousness during the 19th century, because the memory of the past, including the most remote times, was the sign of patriotism.